Production performance of Marwari lambs ubder hot arid region of Rajasthan - DASS, GOPAL; SHARMA, P R; MALHOTRA, VIMAL (The Indian Journal of Animal Sciences, 2011)
The present study was conducted to evaluate growth, wool production and wool quality of Marwari lambs under hot arid climate of Rajasthan. Data on 1626 lambs born between 1998-2002 ’were utilized for analysis. The overall least squares means of body weights at birth, 3, 6,9 and 12 month age were 3.06Â±O.01, 14.35Â±O.05, 19.39Â±O.05, 21.73Â±lO.05 and 24.96Â±O.05 kg, average daily weight gains during 0-3, 3-6, 6-9, 9-12 and 3-12 months were 125.07Â±O.52, 55.24Â±O.59, 39.43Â±0.52, 24.69Â±0.54 and 39.21Â±O.24 g, first and second 6 monthly greasy f1eeee weights were 505.28Â±3.39 and 552.77Â±4.75 g and wool quality paratneters, viz. fibre diameter, hetro fibres, hairy fibres, Inedullation, staple length and crimp were 33.66Â±O.28 Il, 30.46Â±O.68%, 20.27Â±O.52%, 50.72Â±0.90%, 5. 16Â±O.04 ern and O.49Â±O.01/cm respectively. Sex and year of lambing showed significant influence on all the traits except fibre diameter, hetro fibres and medullation. Male lambs were better for all body weights and average daily gains and females were superior in greasy fleece yields and wool quality traits, viz. hairy fibres, staple length and crimp. Year of lambing did not shošpecific trend for any trait under study. Results revealed the importance of pre-weaning (0-3 lTIonth) period that alone contributed about 51.5%of total growth up to 12 months of age. Wool quality parameters indicated suitability of wool for carpet manufaeture. Â